Feasibility of the literacy taxonomy guidebook in the digital age for high school biology teachers - Murni, Odela Priscilia; Afandi, Afandi; Yuniarti, Anisyah; Sulianto, Joko; Sajidan, Sajidan (STKIP Persada Khatulistiwa Sintang, 2025)
Literacy in the digital era has recently become an exciting topic in education policy, research, and practice because it is believed to be the foundation for dealing with life in the digital era. This study aimed to determine the feasibility of the literacy taxonomy guidebook in the digital era for high school biology teachers. The method used is the Research and Development (R&D) model ADDIE, which is limited to the Development stage. Data collection in this study used interview techniques and validation of literacy taxonomy guidebooks in the digital era for high school biology teachers by five validators using validation sheets and reliability tests using ICC. The validated aspects are material, presentation, language, and graphical aspects. This study found that the literacy taxonomy guidebook in the digital era for high school biology teachers received an Aiken validity value of 0.79 with a High Content Validity category, and the average reliability result using the ICC reliability formula was 0.947, with agreement between validators being on the Very Good criteria index. Thus, the literacy taxonomy guidebook in the digital era for high school biology teachers is suitable for teachers to implement literacy in the digital era in biology learning.